2017
DOI: 10.1111/idh.12287
|View full text |Cite
|
Sign up to set email alerts
|

Loss of idealism or realistic optimism? A cross‐sectional analysis of dental hygiene students’ and registered dental hygienists’ professional identity perceptions

Abstract: The fact that dental hygienists had less positive role perceptions than dental hygiene students might lead to the conclusion that a loss of idealism occurs over the course of a professional lifespan. However, dental hygienists actually improved their role perceptions over time and students' future descriptions were more positive than their current descriptions, supporting the interpretation that realistic optimism dominates professional role perceptions in these times of change.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 6 publications
1
2
0
Order By: Relevance
“…They also considered their career prospects to be mapped out, were more motivated toward self-improvement, and were more aware of having career education. These findings support the results of prior studies that found an association between low SOC and early withdrawal from the profession, that student nurses with higher SOC have more excellent career prospects [23], and the recognition of occupational identity among student dental hygienists is positive [24]. Also, the SOC scale has been shown to be effective for coping strategies relating to the view of their profession and for medical career development in student oral health specialists [25,26], suggesting that it might be useful as an indicator of a positive attitude toward the future in student dental hygienists.…”
Section: Discussionsupporting
confidence: 90%
“…They also considered their career prospects to be mapped out, were more motivated toward self-improvement, and were more aware of having career education. These findings support the results of prior studies that found an association between low SOC and early withdrawal from the profession, that student nurses with higher SOC have more excellent career prospects [23], and the recognition of occupational identity among student dental hygienists is positive [24]. Also, the SOC scale has been shown to be effective for coping strategies relating to the view of their profession and for medical career development in student oral health specialists [25,26], suggesting that it might be useful as an indicator of a positive attitude toward the future in student dental hygienists.…”
Section: Discussionsupporting
confidence: 90%
“…Unfortunately, the studies reviewed that include experience as a factor do not take the characteristic of age into account, while in the research sample composed of students there is sometimes a large age difference (Atkins & Gingras, 2009). On the other hand, the professional identity of students and experienced professionals, and how both groups perceive their professional role, is frequently a topic of comparison in studies (Champine et al, 2018). This leads to the conclusion that researchers are not in a position to identify which part of the results are related to professional experience, and which part may also be related to age and corresponding life experience.…”
Section: Aspect 1: Characteristicsmentioning
confidence: 99%
“…9 The SoC is an important psychological resource for professionals involved in health care, 10 and SoC has been confirmed as a significant predictor to burnout or professional identity in nurses. 11,12 For example, Champine et al 13 found that nursing students with higher SoC levels were more likely to have greater career prospects and positive professional perceptions. The level of SoC is affected by the various resources that individuals use in response to stress, which are known as general resistance resources (GRRs, 8 including self-efficacy, 14 resilience, 15 etc.).…”
Section: Introductionmentioning
confidence: 99%